The Effectiveness of Banner as an Educational Media to Increase Mothers' Knowledge about Animal Protein-Rich in Complementary Food for Stunting Prevention - Wirawanti, Ika Wirya; Nadimin, Nadimin; Marwati, St. (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Nutritional intake in toddlers, especially protein, is important because of protein functions as a building nutrient. Toddlers with inadequate protein intake are more at risk of stunting. Education about animal protein-rich in complementary foods for mothers of toddlers is needed to increase the intake of animal protein in toddlers, which can be delivered through an educational media such as banner. This study aimed to analyze the effectiveness of banner as educational media to increase mothers' knowledge about animal protein-rich in complementary food for stunting prevention. This study used a quasi-experimental method with a one group pre test-post test design on mothers of toddlers in the work area of the Tamalanrea Health Center, Makassar. A sample of 44 mothers was selected using purposive sampling based on inclusion criteria, which were mothers with toddlers and willing to participate in this study. The instruments were banner as educational media and questionnaire to assess knowledge before and after the educational intervention. Education was conducted initially through a counseling session using the banner, which was then displayed at the Tamalanrea Health Center as an educational tool. Data were processed and analyzed using SPSS with a paired t-test. The results showed a significant increase in mothers’ knowledge about animal protein-rich in complementary food with the average score rising from 46,6 to 80,7 with a p-value of 0.001. The educational media banner has proven effective in increasing the knowledge of mothers’ about animal protein-rich in complementary food for stunting prevention. The use of similar educational media is expected to be implemented in various health facilities as a promotive and preventive effort in overcoming stunting in Indonesia.